The Effectiveness of the Khanza Application Information System in Documenting Nursing Care in the ICU Room of Prof. Dr. H Aloei Saboe Gorontalo City - Nurmiati Lonang; Hartati Inaku; Rini Asnawati (Universitas Muhammadiyah Palu, 2026)
A health information system is a system where there is quality information, and user satisfaction greatly affects the use of the system and its overall benefits. The Khanza application which is perceived to be of good quality and easy to use will increase nurse satisfaction and have an impact on the completeness of documentation. The method used in this study is observational analysis using the Cross Sectional approach. This describes the variables of the information system of the Khanza Application to the Documentation of nursing care, The sampling technique used in this study uses a non-probability sampling technique with the Total sampling method so that the number of samples in this study amounted to 40 respondents in the ICU room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. From the results of the study, the Khanza application information system in the ICU room from 40 respondents was obtained as many as 31 respondents (77.5%), included in the Good category in the use of information systems and as many as 9 respondents (22.5%) in the poor category. And the results of the study were obtained documentation of nursing care in the ICU room Of the 40 respondents, 31 respondents (77.5%), including in the documentation of complete nursing care and as many as 9 respondents (22.5%) in the documentation of incomplete nursing care. The results of the fisher exact analysis obtained a value of p (0.001) ? 0.05. so it can be concluded that there is an Effectiveness of the Khanza Application Information System in Documenting Nursing Care in the ICU room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City.